Mechanical Signals Induce Dedifferentiation of Mature Adipocytes and Increase the Retention Rate of Fat Grafts. Issue 6 (December 2019) - Ma, Jingjing; Xia, M.D., Jing; Gao, Jianhua; Lu, Feng; Liao, Yunjun
Abstract : Background: Mature adipocytes dedifferentiate in vivo on application of a soft-tissue expander. Dedifferentiated adipocytes can proliferate and redifferentiate. This study used tissue expanders to pretreat adipose flaps, to increase the retention rate after fat graft. Methods: A soft-tissue expander and silicone sheet were implanted beneath the left and right inguinal fat pads of rats, respectively. After 7 days of expansion, the adipose tissue derived from the pads was transplanted beneath dorsal skin. Samples were harvested at various time points, and histologic, immunohistochemical, and gene expression analyses were conducted. Mature adipocytes were cultured in vitro under a pressure of 520 Pa. Changes in cell morphology, the cytoskeleton, and expression of mechanical signal–related proteins were investigated. Results: Pressure in adipose flaps increased to 25 kPa on expansion. Mature adipocytes dedifferentiated following expansion. At 1 week after transplantation, the expression of vascular endothelial growth factor (p < 0.05) was higher in the expanded group. The retention rate at 12 weeks after transplantation was higher in the expanded group (56 ± 3 percent) than in the control group (32 ± 3 percent) (p < 0.05), and the surviving/regenerating zones (p < 0.01) were wider. The lipid content of mature adipocytes gradually decreased on culture under increased pressure, and these cells regained a proliferative capacity. This was accompanied by increased expression of mechanical signal--related proteins (p < 0.05). Conclusions: Mechanical signals may induce dedifferentiation of mature adipocytes. Dedifferentiated adipocytes increase the retention rate of fat grafts by acting as seed cells. Abstract : Supplemental Digital Content is available in the text.